Tingkat Pemahaman dan Peran Guru Pendidikan Anak Usia Dini Terhadap Stunting Di Kepulauan Riau - Abror, Mhd.; Sudarroji, Dwi Rio; Attika, Shidratul; Aisyahfitri, Faradila (Universitas Islam Lamongan, 2024)
Stunting is an issue that is currently a serious concern, the government itself is targeting a stunting prevalence rate of 14% by 2024. The stunting prevalence rate in Kepulauan Riau in 2022 is at 15.4%, this figure has decreased by 2.2% compared to 2021 at 17.6%. However, there are still 5415 cases of stunting in Kepulauan Riau with details of 1110 cases in Karimun, 399 cases in Bintan, 576 cases in Natuna, 535 cases in Lingga, 339 cases in Anambas, 1972 cases in Batam, and 484 cases in Tanjungpinang. Early childhood needs further attention and treatment as an effort to improve and encourage child growth and development. Teachers in PAUD as educational institutions that are in direct contact with children need to have a good understanding of stunting in an effort to help eradicate stunting. The purpose of this study was to determine the level of teacher understanding of stunting, and the role of teachers and efforts that can be made in overcoming the problem of stunting. The method used in this study is Mixed Methods with a Convergent Mixed Methods Design approach analysis model. A total of 256 people became respondents from five regencies/cities in Kepulauan Riau, as many as 255 or 99.6% had a high level of understanding of stunting. Furthermore, PAUD teachers have an important role in dealing with the issue of stunting. Teachers play a role in coordinating with parents. Teachers also play a role in assisting health workers in early detection activities for child growth and development on a regular basis. Teachers also play a role in providing parenting activities with parents about the importance of providing complete and balanced nutrition. Then efforts that can be made to deal with the problem of stunting, including collaborating with integrated health posts and health centers. Furthermore, PAUD teachers are also encouraged to become trained cadres so that they can increase their role in efforts to deal with stunting.